The Link Between Early Involvement with Child Protection System and Youth Offending: A Multi-Agency Data-Linkage Study in Northern Territory, Australia - He, Vincent Yaofeng (International Journal of Population Data Science, 2020)
Introduction Numerous studies have reported a link between child maltreatment and subsequent youth offending leading to calls for early intervention programs focussed on children in contact with child protection services (CPS) as a strategy to reduce the risk offending. While the overlap between child maltreatment and youth offending is well recognised, there have been few studies of the dimensions of CPS involvement that can inform early intervention programs. Whole-of-population linked data provides the opportunity to better understand the characteristics of CPS involvement that predict the risk of offending. Objectives and Approach This retrospective cohort study investigated the association between the level of CPS involvement (no CPS contact through to out-of-home care) for children, before age 10, with youth offending. The study used linked, individual-level records from multiple agencies including birth records, CPS records and youth justice (court) data for 10,438 Aboriginal children born in the NT between 1999 and 2006. Results There was a gradient of increasing risk of youth offending as the level of CPS involvement increased from ‘no report of maltreatment’ to ‘out-of-home care’. There was a similar risk of offending for children with a record of either ‘unsubstantiated’ or ‘substantiated notifications’. Timing of maltreatment (at age 0-4, age 5-9 or both periods) was more strongly associated with offending than whether a notification was substantiated or unsubstantiated. Conclusion / Implications The increased risk of offending associated with different levels of involvement with CPS provides early opportunities for differentiated interventions aimed at reducing the risk of youth offending. Although children with unsubstantiated reports of child maltreatment do not meet the criteria for a statutory response for child protection the increased risk of subsequent youth offending among these children indicates the need to engage families in preventive interventions.